A rare case of giant urethral calculus and multiple urethral diverticulum - Agarwal, A; Sigdel, G; Belokar, WK (Journal of College of Medical Sciences-Nepal, 2012)
Urethral stones in adults are rare and usually encountered with urethral stricture or diverticulum. We report a 54 years old gentleman who presented with urinary retention due to a large urethral calculus impacted in bulbar urethra with multiple stones in anterior and posterior urethral diverticulum. On examination a mass of size 5.5cmx4cmx3cm was palpable at anterior perineum with a fistulous tract from which pus was oozing out. On retrograde urethrogram a large urethral calculus with bulbar diverticulum and multiple radio opacity in prostatic area were revealed. Patient was managed by suprapubic cystostomy initially and later on by external urethrotomy, diverticulectomy, urethroscopic removal of multiple stones in prostatic urethral diverticulum and urethroplasty. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 46-48 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6838